Filling in the Flyover Zone: High Phosphorus in Midwestern (USA) Reservoirs Results in High Phytoplankton Biomass but Not High Primary Productivity - Petty, Erin L.; Obrecht, Daniel V.; North, Rebecca L. (Frontiers in Environmental Science, 2020)
In lakes and reservoirs, climate change increases surface water temperatures, promotes thermal stability, and decreases hypolimnetic oxygen. Increased anthropogenic land-use and precipitation enhance nutrient and sediment supply. Together, these effects alter the light and nutrient dynamics constraining phytoplankton biomass and productivity. Given that lake and reservoir processes differ, and that globally, reservoir numbers are increasing to meet water demands, reservoir-centric studies remain underrepresented. In the agricultural midwest (USA), ubiquitous reservoirs experience eutrophy and hypolimnetic anoxia. Here, we explore influences of eutrophication and land-use on the proximate light and nutrient status of phytoplankton communities in 32 Missouri reservoirs. Light and nutrient status indicators include mixed layer irradiance, phosphorus (P) and nitrogen (N) stoichiometry/debts, photosynthetic efficiency, and photosynthetic-irradiance parameters. Contributing to the ongoing P versus N and P management debate, we evaluate if phytoplankton biomass and productivity are constrained by light, P, N, or a combination thereof, across gradients of trophic status and land-use during 2 contrasting wet and dry summers. Despite agricultural prevalence, P-deficiency is more prominent than either N- or light-deficiency. In 2018, ~46% of samples were P-deficient with ~36% indicating neither light nor nutrient deficiency. Gross primary productivity per unit chlorophyll-a (GPPB) demonstrated negative relationships with nutrients, biomass, and turbidity, and positive relationships with light availability. Subsequently, GPPB was highest in oligotrophic reservoirs where light utilization efficiency was also highest. Overall, phytoplankton biomass and productivity appear constrained by P and light, respectively. If midwestern reservoirs are precursors of future inland waters affected by climate change and eutrophication, our crystal ball indicates that both P and light will be important regulators of phytoplankton dynamics and subsequent water quality.